Patient acceptance of an electronically recruited beta blocker trial. (14th October 2021) - Denman, J; Roebuck, A; Lee, K; ,
Abstract: Background: Beta Blockers (BB) have been the standard of care after acute myocardial infarction (AMI) since the 1960's. There is good evidence of clinical effectiveness in the post AMI patient with impaired left ventricular function. However, there is little contemporary evidence in the post AMI patient with preserved left ventricular function. Data suggests that BB in preserved left ventricular function may not convey clinical benefit and indeed there is a suspicion that they may cause harm. BB are acknowledged to be associated with side effects that impact on patient's health related quality of life (HRQoL). Purpose: NICE Guidelines for ACS (2020) recommend further research in this topic. We wanted to understand current UK practice. Whether patients felt further research was needed and if they would be likely to consent and participate in an electronic RCT? Methods: Professional practice and patient experience was solicited using a purposeful mixed methodological electronic survey of x15 English Heart Attack Centres, x7 Primary Care Networks and cardiac support groups contacted via the British Heart Foundation Cardiac Support Group network. Results: n=598 surveys were distributed with a response rate of 26% (n=157). In secondary care only 8% of patients routinely were reviewed. In primary care 73% of patients were reviewed. Across both provider localities 90% of respondents had not discussed stopping their beta blockers at x1 year. 20% of patients experienced side effects attributable to BB. Primary care reported that they were consulted at least once per week by a patient with side effects likely to be from their BB. Patients reported side effects the severely impacted on HRQoL including tiredness/lethargy, reduced exercise tolerance, light-headedness and impotence. 86% of patients stated they would like to participate in further research. Of these responders 96% stated they would have been happy to have been contacted via an electronic record search. Most respondents preferred electronic communication. Discussion: Despite lack of evidence for their clinical effectiveness in patients x1 year post AMI with preserved left ventricular function most patients had their therapy continued. Both patients and clinicians' report a high symptom burden impacting on HRQoL and health economics. Patients reported that given the lack of evidence they would welcome a discussion if they should continue BB therapy or not. Most nations have databases of their post AMI patients. Electronic recruitment into an RCT from a database would reduce trial costs and the enrolment period. Respondents felt there was a need for further research. They were happy to be contacted after a database search and preferred electronic communication. These responses have significant implications for further large scale research and support the concept of enrolment in to a RCT via database interrogation. Funding Acknowledgement: Type of funding sources: None.